2012
DOI: 10.1007/s11224-012-0051-x
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of the linear relationship between SWCNTs functionalization energies and sidewall curvature

Abstract: A simple linear relationship between the functionalization reaction energies for the exohedral monovalent addition on the surface of an ideal, infinitely long, single-walled carbon nanotube (SWCNT) and the reciprocal SWCNT radius has been derived employing the hardsoft acid basis principle and the tight binding model. The slope of the derived linear relationship is a function of the effective number of valence electrons involved in the functionalization reaction. The intercept of the derived linear relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…As fragmentation, particularly for the large species, requires high levels of internal energy, delayed fluorescence may play more of a role. Following Berné et al (2015), and adopting a binding energy of 4.6 eV and an energy gap of 2.1 eV (Fusaro 2012), we have examined the possible effect of electronic relaxation on the H-loss rate of large PAHs. As an example, for circumcoronene, at an internal energy of 25 eV the H-loss rate is calculated to be 5 × 10 4 s −1 , which should be compared to the electronic relaxation rate of ∼0.5 s −1 and the IR relaxation rate of ∼1 s −1 .…”
Section: Photodissociation Channelsmentioning
confidence: 99%
“…As fragmentation, particularly for the large species, requires high levels of internal energy, delayed fluorescence may play more of a role. Following Berné et al (2015), and adopting a binding energy of 4.6 eV and an energy gap of 2.1 eV (Fusaro 2012), we have examined the possible effect of electronic relaxation on the H-loss rate of large PAHs. As an example, for circumcoronene, at an internal energy of 25 eV the H-loss rate is calculated to be 5 × 10 4 s −1 , which should be compared to the electronic relaxation rate of ∼0.5 s −1 and the IR relaxation rate of ∼1 s −1 .…”
Section: Photodissociation Channelsmentioning
confidence: 99%
“…A linear relationship is observed between and the tube curvature, in agreement with previous electronic structure calculations on neutral adsorbents. Indeed, it has been shown that depends linearly on the tube curvature by means of the relation: ,, where the positive and negative sign applies for exo- and endohedral adsorption, respectively. The monotonic increase in energy with 1/ R was attributed to the surface pyramidalization that contributes to a local rehybridization from sp 2 to sp 3 at the adsorption site C 0 , thus favoring chemical interactions in the exohedral case and unfavoring them in the endohedral one. , Therefore, the narrower the tube, the higher the pyramidalization at the exohedral adsorption site.…”
Section: Resultsmentioning
confidence: 99%